Radiofrequency current catheter ablation of accessory atrioventricular pathways - Trajkov, I; Kovacevic, D; Boskov, V; Poposka, Lidija; Gjorgov, N (My University, 2006)
The purpose of this study was to evaluate the safety and efficacy of a radiofrequency catheter ablation in the patients with the Wolff-Parkinson-White syndrome or paroxysmal supraventricular tachycardia involving a concealed accessory atrio ventricular connection.